2022
DOI: 10.18632/aging.204050
|View full text |Cite
|
Sign up to set email alerts
|

Expression status and prognostic significance of mitochondrial dynamics OPA3 in human ovarian cancer

Abstract: Early diagnosis of ovarian cancer and the discovery of prognostic markers can significantly improve survival and reduce mortality. OPA3 protein exists in a structure called mitochondria, which is the energy production center of cells, but its molecular and biological functions in ovarian cancer are still unclear. Here, the expression of OPA3 mRNA in ovarian cancer was estimated using TCGA, Oncomine, TIMER databases. We found that functional OPA3 activation caused by mutations and profound deletions predicted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Recently, a high level of OPA3 protein has been reported in ovarian cancer tissues and cells [ 111 ]. The OPA3 gene was first identified in patients with optic neuropathy, and encodes for an OPA3 protein that is a mitochondrial protein involved in the shape and structure of the mitochondria [ 112 ].…”
Section: Mitochondrial Dynamics In Ovarian Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a high level of OPA3 protein has been reported in ovarian cancer tissues and cells [ 111 ]. The OPA3 gene was first identified in patients with optic neuropathy, and encodes for an OPA3 protein that is a mitochondrial protein involved in the shape and structure of the mitochondria [ 112 ].…”
Section: Mitochondrial Dynamics In Ovarian Cancermentioning
confidence: 99%
“…The OPA3 gene was first identified in patients with optic neuropathy, and encodes for an OPA3 protein that is a mitochondrial protein involved in the shape and structure of the mitochondria [ 112 ]. The high expression of OPA3 mRNA and protein levels in OC are associated with poor prognosis [ 111 ]. Importantly, it was reported that OPA3 inactivation increased sensitivity of ovarian cancer cells to PFI-1 and WZ4003 antiproliferative drugs [ 111 ].…”
Section: Mitochondrial Dynamics In Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The TMA slides consisted of samples of human gastric cancer, metastatic cancer, and normal tissues. To conduct immunocytochemistry (ICC) on the TMA slides, we followed the protocol described in a previous study [32,33]. A uorescent multiplex staining kit (BioTnA, TATS01F, Kaohsiung, Taiwan) along with speci c antibodies are utilized in labeling and detecting desired proteins in tissue samples for ICC.…”
Section: Human Stad Tissue Microarrays and Immunocytochemistry Analysismentioning
confidence: 99%
“…Ovarian cancer is among the most lethal gynaecological malignancies [ 1 ]. It involves a heterogeneous group of malignancies that differ in aetiology, molecular biology, and many other characteristics [ 2 , 3 ]. Approximately, 90% of ovarian cancers are of epithelial origin, and the prevalent subtype of epithelial ovarian cancer is serous carcinoma [ 4 ].…”
Section: Introductionmentioning
confidence: 99%